2003
DOI: 10.1016/s0269-7491(02)00480-3
|View full text |Cite
|
Sign up to set email alerts
|

Trace elements in two odontocete species (Kogia breviceps and Globicephala macrorhynchus) stranded in New Caledonia (South Pacific)

Abstract: Liver, muscle and blubber tissues of two short-finned pilot whales (Globicephala macrorhynchus) and two pygmy sperm whales(Kogia breviceps) stranded on the coast of New Caledonia have been analysed for 12 trace elements (Al, Cd, Co, Cr, Cu. Fe, organic and total Hg, Mn, Ni, Se, V, and Zn). Liver was shown to be the most important accumulating organ for Cd, Cu, Fe, Hg, Se, and Zn in both species, G. macrorhynchus having the highest Cd, Hg, Se and Zn levels. In this species, concentrations of total Hg are partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 31 publications
7
45
0
2
Order By: Relevance
“…Elevated environmental Hg concentrations have been widely documented in marine biota and extreme levels are regularly reported (Bustamante et al 2003; Kim et al 1996). The direct effects of elevated MeHg on marine biota can include impacts on neurologic end points and memory, locomotion, and cognition, as well as changes in brain neurochemical receptor density (Basu et al 2005; Scheuhammer et al 2008).…”
Section: Trophic Transfer and Bioaccumulation Of Mehg In Marine Food mentioning
confidence: 99%
“…Elevated environmental Hg concentrations have been widely documented in marine biota and extreme levels are regularly reported (Bustamante et al 2003; Kim et al 1996). The direct effects of elevated MeHg on marine biota can include impacts on neurologic end points and memory, locomotion, and cognition, as well as changes in brain neurochemical receptor density (Basu et al 2005; Scheuhammer et al 2008).…”
Section: Trophic Transfer and Bioaccumulation Of Mehg In Marine Food mentioning
confidence: 99%
“…Binding of Se to Hg may reduce the bioavailability of Se and its antioxidant, antiviral, antimutagenic and anti-carcinogenic properties are consequently reduced, resulting in an increased susceptibility of marine mammals to oxidative injury (Ralston and Raymond, 2010). Se occurs at 1:1 M ratios with Hg in several marine mammal tissues such as liver, kidney and brain Bustamante et al, 2003). Ralston and others authors (Peterson et al, 2009;Ralston and Raymond, 2010;Sørmo et al, 2011) have suggested that excess selenium protects against mercury toxicity, and that Se:Hg molar ratios above 1 are largely protective for adverse effects related to mercury consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Increased levels of trace elements are indicative of bioaccumulation of heavy metal toxins, mainly in liver tissues. Many fish species are threatened by such toxins and they are used to investigate the impact of environmental pollution [3][4][5] .…”
Section: Chemometric Classification Of Some Elements In Wild and Farmmentioning
confidence: 99%